Goal-Setting as leadership strategy in public service media organization – between individual motivation and public mandate - Rimscha, M.B.; Medina, M.; Crespo, M.; Voci,D.; Karmasin, M. (European Media Management Association anual conference, 2023)
Public service media organization offer media content that at times is quite similar to that offered by commercial media. However, a public service media organization’s mission is not to maximize profit but rather (depending on national legislation) to maximize societal benefit. While this is intuitively comprehensible on the organizational level, the question arises what this organizational mission entails in terms of human resource management and leadership. Does knowledge about how to motivate staff and how motivations might influence performance apply here? Or does the difference in the organizational goal call for a completely different approach? This question is especially relevant at a time where public service media organizations are under pressure. Fees are under scrutiny or replaced by tax funded grants at the grace of politicians and often it is demanded that the organizations should become more efficient. While some politicians outright reject the idea of public service media and want to scrap much of the organization and its offerings, others have a more nuanced approach when they demand more focus on the organizations public goal and ways to achieve it with limited budgets. Hence aligning human resource (HR) management concepts with the organizational goals might be a way to make public service media more efficient and less prone to allegations of waste and the resulting politic pressure. In public management as a related field, some authors suggest a different type of personnel would be needed in this sector. They should have a public service motivation even before starting to work for the government or administration and would thus be drawn to the respective jobs (e.g. Perry & Wise, 1990). Therefore, the HR task would be selecting the right staff upfront rather than motivating them later on. Other authors suggest a public service motivation could also develop only after starting to work in the public sector when the public organizations’ mission is perceived as important (e.g. Wright, 2007). Empirical evidence in this context is mixed: For example in an early study Rainey (1982) found that public sector managers would care less about monetary rewards while later Alonso and Lewis (2001) found that government employees with a high PSM reacted all the same on material rewards. In a large scale review of the field Ritz, Brewer and Neumann (2016) report that studies on the outcomes of public service motivation predominantly show positives effects both for the individual and for the organization. The notion of special characteristics of staff is also supported by research on journalists and their orientations. Studies regularly find that journalist both in commercial and in public service media would show an orientation towards a public interest (Hanitzsch et al., 2019; e.g. Marr et al., 2001; Weischenberg et al., 2006). Journalistic and creative staff show high levels of intrinsic motivation. Thus, the effect of performance-based pay schemes is likely to be limited. Several scholars in the context of creative work even suggest a negative effect extrinsic motivation (Frey, 2002). But what about media managers in public service media organizations can they be motivated by goal setting and the respective incentives be they monetary or non-material? This article tries to answer this research question. It is structured as follows: First we conduct an extensive literature review on goal-setting and incentives and how they relate to performance. We put special emphasis on studies that have looked into settings with organizational goals other than profit maximization. Second and based on this literature we derive how goal setting might be a useful human resource tool also in the management of public service media organizations. Third we present examples form different European public service broadcasters to illustrate how and how successful (or not) goal setting and performance related incentives are implemented. In the last section we will discuss in how far the examples support the notion of goal-setting as a useful tool in a public service media context or not and whether generalizations are possible concerning favorable conditions or typical constraints.